Characteristics of the competitive activity of football players of various game roles in youth national teams - Kalinin, E. M.; Kuzmichev, V. A.; Khomyakova, A. A.; Leksakov, V. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the characteristics of the competitive activity of players of different roles in national teams based on data received from GPS equipment.